2021
DOI: 10.3390/universe8010002
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dark Solitons in the 1D Bose Gas: From Single to Double Dark-Solitons

Abstract: We study quantum double dark-solitons, which give pairs of notches in the density profiles, by constructing corresponding quantum states in the Lieb–Liniger model for the one-dimensional Bose gas. Here, we expect that the Gross–Pitaevskii (GP) equation should play a central role in the long distance mean-field behavior of the 1D Bose gas. We first introduce novel quantum states of a single dark soliton with a nonzero winding number. We show them by exactly evaluating not only the density profile but also the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…We note that the density profile shown in panel (a) of figure 2 is identical to the upper-left panel of figure 9 for c = 0.05 in [22]. In the latter panel it was shown that the density profile of the quantum double dark-soliton state completely coincides with the density profile of the elliptic double dark-soliton solution of the GP equation.…”
Section: Time Evolution Of Quantum Double Dark-soliton State Construc...supporting
confidence: 61%
See 4 more Smart Citations
“…We note that the density profile shown in panel (a) of figure 2 is identical to the upper-left panel of figure 9 for c = 0.05 in [22]. In the latter panel it was shown that the density profile of the quantum double dark-soliton state completely coincides with the density profile of the elliptic double dark-soliton solution of the GP equation.…”
Section: Time Evolution Of Quantum Double Dark-soliton State Construc...supporting
confidence: 61%
“…A quantum state that has two notches in both profiles of density and square amplitude of the matrix element of the field operator was proposed in [22]. We call it the quantum double darksoliton state, and it is given by the superposition of 'two-hole' excitation states as follows:…”
Section: Quantum Double Dark-soliton Statementioning
confidence: 99%
See 3 more Smart Citations